Patellar cartilage lesions: comparison of magnetic resonance imaging and T2 relaxation-time mapping - Hannila, I; Nieminen, M T; Rauvala, E; Tervonen, O; Ojala, R (Acta radiologica (1987), 2007)
To evaluate the detection and the size of focal patellar cartilage lesions in T2 mapping as compared to standard clinical magnetic resonance imaging (MRI) at 1.5T. Fifty-five consecutive clinical patients referred to knee MRI were imaged both with a standard knee MRI protocol (proton-density-weighted sagittal and axial series, T2-weighted sagittal and coronal series, and T1-weighted coronal series) and with an axial multislice multi-echo spin-echo measurement to determine the T2 relaxation time of the patellar cartilage. MR images and T2 maps of patellar cartilage were evaluated for focal lesions. The lesions were evaluated for lesion width (mm), lesion depth (1/3, 2/3, or 3/3 of cartilage thickness), and T2 value (20-40 ms, 40-60 ms, or 60-80 ms) based on visual evaluation. Altogether, 36 focal patellar cartilage lesions were detected from 20 human subjects (11 male, nine female, mean age 40+/-15 years). Twenty-eight lesions were detected both on MRI and T2 maps, while eight lesions were only visible on T2 maps. Cartilage lesions were significantly wider (P = 0.001) and thicker (P<0.001) on T2 maps as compared to standard knee MRI. Most lesions 27 had moderately (T2 40-60 ms) increased T2 values, while two lesions had slightly (T2 20-40 ms) and seven lesions remarkably (T2 60-80 ms) increased T2 relaxation times. T2 mapping of articular cartilage is feasible in the clinical setting and may reveal early cartilage lesions not visible with standard clinical MRI.